B403 Peripheral nerve block for phantom limb pain – more than a temporary fix. (11th August 2022) - Sales, F; Maldonado, AF; Torres, J
Abstract : Background and Aims: Phantom limb pain is associated with depression, poor quality of life, and work incapacity. Despite being a relatively widespread condition, it still presents a challenge and is often poorly responsive to treatment. Methods: We report the successful use of a single-shot peripheral nerve block in a patient with phantom toe pain. A 35-year-old obese woman with psoriasis was referred to the Chronic Pain Unit due to neuropathic pain in the left foot with phantom pain in the 2nd toe. She had a history of pyoderma gangrenosum circumscribed to the left foot and required 2nd toe amputation 4 years prior. She described intense stabbing and pinprick pain in the sole and lateral region of the foot, with allodynia and hyperalgesia. The pain was worsened by walking (10/10 vs 3/10 at rest) and cold. The patient had been prescribed gabapentin which she did not tolerate, and tramadol + dexketoprofen which caused hepatic toxicity. We performed an ultrasound-guided posterior tibial nerve block and deep and superficial peroneal nerve block with 0.2% ropivacaine. Results: The next day, the pain improved significantly (2/10) and phantom pain ceased. The patient was able to return to work as a factory employee one month after the procedure, the pain remained controlled with oral medication only. Phantom pain never recurred during the one-year follow-up. Conclusions: Peripheral nerve blocks are valuable techniques in phantom pain management. A single-shot nerve block may relieve phantom pain for an extended period and allow patients to return to work.